OHP-081 Use of Low Therapeutic Utility Drugs in an Institution Before Their Use Was Restricted in the Spanish Health System. (12th March 2013) - Arribas-Díaz, B; Bosó-Ribelles, A; Moregó-Soler, MA; Sánchez-Mulero, MC; Tobaruela-Soto, M; Selvi-Sabater, P; Rizo-Cerdá, AM; Sánchez-Catalicio, MM; Molina-Guillén, MP; Ramón-Manresa, N
Abstract : Background: Low therapeutic utility drugs (LTUDs) are those with controversial efficacy that provide little improvement for the disease or the symptoms. These drugs have recently been removed from the system financing Spanish healthcare, with the aim of controlling healthcare expenditure. Purpose: To assess the use of these drugs in institutionalised older people and find out how the new law may be affecting it. Materials and Methods: This was a retrospective transversal study. We choose one day at random and checked all treatments prescribed that day. The following data were collected: drugs, sex, age and LTUDs. The data were obtained from the SAVAC programme and processed in Excel. Results: A total of 175 residents were included, mean age 89 years old. LTUDs were administered to 65 people (37%). There were 1812 different drugs, of which 88 (4.9%) were LTUDs, measured as number of dosage units. Drug consumption in primary care (PC) is measured by number of packs, not as number of dosage units. During the study, PC consumption of LTUD accounted for 6.86% of the total. The LTUDs prescribed were: 26 items (30.3%) acetylcysteine, 18 (21.5%) topical diclofenac, 12(14.4%) citicoline, 10 (12.0%) trimetazidine, 9 (10.8%) pentoxifylline, 4 (4.9%) piracetam, 2 (2.5%) ambroxol, 1 (1.2%) acetaminophen plus codeine, 1(1.2%) escine and 1(1.2%) inhaled mesna. Conclusions: Institutionalized older people use fewer LTUDs than patients from PC. Mucolytic agents and topical NSAIDs are on top of the list, accounting for 50% of the LTUDs used. Nearly 40% of institutionalised people will have to pay for these 5% of their drugs, or these medicines will have to be removed from their treatments. Better designed studies should be done to clarify the real efficacy and efficiency of this large group of drugs. No conflict of interest.